Factors affecting the occurrence and activity of clouded leopards, common leopards and leopard cats in the Himalayas - Can, E; Bhupendra, Y; Ross, J; D'Cruze, N; Johnson, P; Macdonald, D (Springer, 2019)
Clouded leopards are one of the least known of larger felids and were believed to be extinct in Nepal until 1987. They are particularly interesting because their Asian range spans a diversity of habitats in the fastest disappearing forests in the world and encompasses a guild which differs in composition from place to place. As a part of a wider camera-trapping study of this guild, involving 2948 camera traps at 45 sites in nine countries, and paralleling a similar study of the Sunda clouded leopard including a further 1544 camera traps spanning 22 sites distributed across two countries, we deployed 84 pairs of camera traps for 107 days in 2014 and 2015 at Langtang National Park, Nepal between 1823 and 3824 m a.s.l. within a grid encompassing c. 120 km2. We documented the presence of clouded leopards for the first time at an altitude as high as 3498 m a.s.l. Naïve occupancy for clouded leopard was 8.6% (correcting for detection, 10.1%). Clouded leopards were least active in the middle of the day, and largely crepuscular and nocturnal, as were the common leopards and leopard cats. The peak of clouded leopard activity overlapped with that of musk deer. Prey species for both clouded leopard and common leopard were available across the elevation range studied although the availability of some prey species declined as elevation increased, whereas Himalayan serow, Himalayan goral, and musk deer showed no association with elevation. Before this study, there was no hard evidence that clouded leopards occurred above 2300 m a.s.l., having documented them at almost 4000 m a.s.l. in the Himalayas, we emphasise the importance of this extreme portion of the species’ range where climate is likely to change more rapidly and with greater consequences, than the global average. The discovery of clouded leopards in Langtang National Park considerably extends their known range, and raises the possibility that they occur from the Terai in southern Nepal up to the Nepal-Tibet (China) border in the north. Insofar as this study has extended the known extreme boundary of the clouded leopard’s geographic range to encompass Langtang National Park in the Nepali Himalayas.